Letter to Jane Tolmach from Leo T. McCarthy - Leo T. McCarthy:::::: (1976)
In a May 24, 1976 letter, Assembly Speaker Leo T. McCarthy informed Jane Tolmach that he was enclosing "another piece of good news" regarding her campaign. He advised her to contact A. Dan Reilly, chairman of the United Transportation Union (UTU), directly. The brief note reflects McCarthy's continued support and facilitation of campaign endorsements or assistance.